Some experiments on modeling stock market behavior using investor sentiment analysis and posting volume from twitter - Oliveira, Nuno (2013)
The analysis of microblogging data related with stock mar- kets can reveal relevant new signals of investor sentiment and attention. It may also provide sentiment and attention indicators in a more rapid and cost-effective manner than other sources. In this study, we created several indicators using Twitter data and investigated their value when model- ing relevant stock market variables, namely returns, trading volume and volatility. We collected recent data from nine ma jor technological companies. Several sentiment analy- sis methods were explored, by comparing 5 popular lexical resources and two novel lexicons (emoticon based and the merge of all 6 lexicons) and sentiment indicators produced using two strategies (based on daily words and individual tweet classifications). Also, we measured posting volume associated with tweets related to the analyzed companies. While a short time period is considered (32 days), we found scarce evidence that sentiment indicators can explain these stock returns. However, interesting results were obtained when measuring the value of using posting volume for fit- ting trading volume and, in particular, volatility.